Gender Difference and Correlates of Physical Activity Among Urban Children and Adolescents in Ethiopia: A Cross-Sectional Study - Biadgilign, Sibhatu; Gebremichael, Bereket; Abera, Admas; Moges, Tsedey (Frontiers in Public Health, 2022)
Background Studies indicate that children and adolescent populations in most countries show a low level of physical activity (PA) and an increasing prevalence of obesity. Addressing gender disparity in PA is the main element of public health programs. There is currently a paucity of studies, particularly, in developing countries that investigate gender differences and correlates of PA among children and adolescents. Objective The study is aimed to assess the gender difference and correlates of PA among children and adolescents in Ethiopia. Methods An observational population-based cross-sectional study was conducted in representative samples of children and adolescents in the capital city of Ethiopia, Addis Ababa. Multivariable logistic regression models with robust estimation of SEs were fitted to predict the odds ratios (ORs) and 95% CIs. Results A total of 632 children and adolescents-parent dyads were included in the study. More boys than girls (17.0 and 11.7%) were engaged in moderate intensity PA 3 days a week or more (p = 0.057). Age, mothers working in a private business, attending public schools, longer sleep duration, and being taught the benefits of PA were positively associated with meeting moderate-to-vigorous PA (MVPA) in both sexes combined and in a sub-sample of boys. Furthermore, an inverse association was found between overweight/obesity and MVPA in the overall children and girls as well. For moderate PA (MPA); the age of the children, maternal education and occupation, school type, overweight/obesity, and sleep duration on school nights were significant correlates among the studied children. Conclusions The present study provided evidence of several correlates identified associated with meeting MVPA and MPA in both sexes combined. Girls are less likely than boys to engage in PA. Therefore, there is a need to take into perspectives the provision of a comprehensive multifaceted health behavior modification and interventions, such as focused and regular physical education in schools.